Mandatory Legal Understanding for Government Officials to Realize Good Governance - Maisondra; Ahmad Redi (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2025)
The lack of legal knowledge and understanding among government officials in Indonesia can lead to poor governance, corruption, and abuse of authority, ultimately affecting the quality of public services and public trust in the government. The purpose of this study is to emphasize the importance of mandatory legal knowledge for government officials in realizing good governance and to identify the need for increased sanctions for government officials who violate the law. The theories used in the analysis are: Principles of Good Governance and the Concept of Mandatory Legal Knowledge. This study uses a normative legal research method with a literature review approach, analyzing relevant laws, regulations, and legal theories, with a qualitative descriptive approach. The study highlights the importance of legal knowledge for government officials in carrying out their duties effectively and efficiently, and the need for increased sanctions for government officials who violate the law to improve accountability and transparency. Mandatory legal knowledge for government officials is crucial for realizing good governance, and increased sanctions for government officials who violate the law can improve accountability, transparency, and public trust in the government. Additionally, this research is expected to contribute to the improvement of legal knowledge and understanding among government officials, and to provide recommendations for policymakers to enhance the quality of public services and promote good governance in Indonesia.